PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP TURNOVER INTENTION - Widayati, Catur; Yunia, Yolanda (Jurnal Manajemen, 2016)
This study aims to determine the effect of compensation and organizational culture on turnover intention. The object of this study are employees of the company PT HadicoPersada with businesses engaged in outsourcing, located in Central Jakarta. This study was conducted on 47 respondents. The sampling technique used in this study is saturated samples. Therefore, the analysis of the data used is the statistical analysis in the form of multiple linear regression tests. These results indicate that partially, the variable compensation has a negative and significant impact on the variable turnover intention. Variable organizational culture has a significant negative effect on the variable turnover intention.